Testing 4-critical plane and projective plane multiwheels using Mathematica - Zeps, Dainis (My University, 2015)
In this article we explore 4-critical graphs using Mathematica. We generate graph patterns according [1, D. Zeps. On building 4-critical plane and projective plane multiwheels from odd wheels, arXiv:1202.4862v1]. Using the base graph, minimal planar multiwheel and in the same time minimal according projective pattern built multiwheel, we build minimal multiwheels according [1], Weforward two conjectures according graphs augmented according considered patterns and their 4-criticallity, and argue them to be proved here if the paradigmatic examples of this article are accepted to be parts of proofs.
Keywords: graph theory, critical graphs, wheels, Grötsch graph, planar graphs, projective plane graphs